Hubungan Interaksi Dalam Keluarga dengan Kepercayaan Diri Remaja di Jorong Cupak Nagari Pakan Sinayan - Fitri, Gita; Yarni, Linda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the phenomenon of interaction in the family with adolescent selfconfidence in Jorong Cupak Nagari Pakan Sinayan. There are teenagers who do not get good support from their families in carrying out an activity, besides that there are teenagers who do not have good interactions with family members. Meanwhile, with adolescent self-confidence, there is a phenomenon that there are still many teenagers who find it difficult to interact with the surrounding environment. This study aims to look at the interactions of adolescents aged 13-19 years in Jorong Cupak, to see the self-confidence of adolescents aged 13-19 years in Jorong Cupak, and to see the relationship between interactions in the family and the self-confidence of adolescents in Jorong Cupak Nagari Pakan Sinayan. This type of research is correlationalquantitative research. The results showed that the interaction in the family of adolescents aged 13-19 years in Jorong Cupak Nagari Pakan Sinayan was declared good with a percentage of 45.8%,the self-confidence of adolescents aged 13-19 years in Jorong Cupak Nagari Pakan Sinayan wasdeclared good with the percentage is 34.8%, and the relationship between adolescent interactionin the family and adolescent self-confidence in Jorong Cupak Nagari Pakan Sinayan has a closerelationship, which is 72%.